Multifocal Recurrent Osteomyelitis and Hemophagocytic Lymphohistiocytosis in a Boy with Partial Dominant IFN-γR1 Deficiency: Case Report and Review of the Literature - Staines-Boone, Aidé Tamara; Deswarte, Caroline; Venegas Montoya, Edna; Sánchez-Sánchez, Luz María; García Campos, Jorge Alberto; Muñiz-Ronquillo, Teodoro; Bustamante, Jacinta; Espinosa-Rosales, Francisco J.; Lugo Reyes, Saul Oswaldo (Frontiers in Pediatrics, 2017)
Mutations in the genes coding for cytokines, receptors, second messengers and transcription factors of interferon gamma immunity cause Mendelian susceptibility to mycobacterial disease (MSMD). We report the case of a 7-year-old male patient with partial dominant interferon gamma receptor-1 deficiency who had suffered from multifocal osteomyelitis attributable to BCG vaccination since the age of 18 months. He developed hemophagocytic lymphohistiocytosis (HLH), a hyper-inflammatory complication, and died with multiorgan dysfunction, despite having been diagnosed and treated relatively early. Patients with partial dominant interferon receptor deficiency usually have good prognosis and might respond to human recombinant subcutaneous interferon gamma. Several monogenic congenital defects have been linked to HLH, a catastrophic “cytokine storm” that is usually ascribed to lymphocyte dysfunction, and thought to be triggered by interferon gamma. This is the sixth patient with both MSMD and HLH of whom we are aware. The fact that patients with macrophages that cannot respond to IFNG still develop HLH, bring these assumptions into question, and suggest the need for further study to better understand and treat HLH.